UPAYA PENINGKATAN PRESTASI BERMAIN BOLA BASKET MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Zaidin, Zaidin (Jurnal Pembelajaran Prospektif, 2020)
The development of sports in schools is really needed to improve the students’achievements of SMP Negeri 1 Matan Hilir Selatan, at its increased level. Seeing its success on basketball, it still needs very serious coaching to pursue the achievements. To achieve the desired performance certainly requires training, both technical trainings and tactics to strengthen the match team. For this, discipline, sportsmanship, the courage to work together and responsibilities are highly expected because in basketball games there are many rules that must be implemented, such as movements for throwing, catching, dribling, and shooting. There are several alternatives to come out with the method of playing like searching what problems of not understanding all movements Power (explosive power) and speed of reactivity, agility as well flexibility. In carrying out something work must have a purpose, so there is no deviation that can reach its goal as well in the implementation of this study. The authors have the purpose of knowing the relationship between speeding and dribling in the basketball skills by players. This research was conducted in Classroom Action Research Design.(CAR)